The Impact of Microwave Treatment on the Chemical Properties of Sewerage Sludge - Doh, Shu Ing; Putra Jaya, Ramadhansyah; Chia, Min Ho; Siew, Choo Chin; Nabiałek, Marcin; Mohd Mustafa Al Bakri, Abdullah; Garus, Sebastian; Śliwa, Agata (Polish Academy of Sciences, 2022)
Due to urbanization, the population in the major cities in Malaysia is approximately 72.8% of its total population. The increase of population density has directly increased the amount of sewerage sludge waste that poses threat to the environment. In line with the green initiatives, alternative method to develop good quality concrete material from sewerage sludge waste can be further explored. Traditionally, sewerage sludge waste is processed using incinerator that require high energy and it is time consuming. In this study, microwave heating which require less energy consumption and less time consuming is used for sewerage sludge preparation. Prior to heating process, sewerage sludge waste is over dried at 105◦C for 24 hours. Three types of microwave heating namely medium heating, medium high heating and high heating has been used. The chemical and physical properties microwaved sewerage sludge ash (MSSA) was tested using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). Based on the result, the recommended temperature for the MSSA production for the concrete is High Mode Temperature. This is due to the result of MSSA for X-Ray Fluorescent test as its shows the highest in the content for pozzolanic element which are SiO2 and Fe2O3 that produce after the microwave burning process. The mineralogical composition and the crystalline phase of the High temperature MSSA due to X-Ray Diffraction test also shows high content of SiO2 as the major component as it is good for pozzolanic reaction in concrete. From the Scanning Electron Microscope test, it is observed that particle of High heated MSSA are slightly smaller than other temperature. Also, the densification occurs at High temperature MSSA. Hence, the optimal burning temperature mode for MSSA is High Mode temperature